(untitled) (Bangladesh Pharmaceutical Journal, 2013)
Diabetes associated dyslipidemia is one of the major causes of disability in western as well as in developing countries. The present study was designed to investigate the effect of ethanolic extract of Hibiscus rosa sinensis (EHBS) leaves on alloxan-induced diabetes with dyslipidemia in rats. Treatment of alloxan-induced diabetes with most effective observed dose (2.0 mg/kg body weight) of EHBS for 1 week significantly reduced glucose level, TC, TG and LDL-C, with the increase of HDL-C and weight of kidney, pancreas and liver when compared with diabetic rats. The observation was also made for consecutive 4 weeks to confirm the results obtained in one week model. Like one week, we got similar results when the treatment of alloxan-induced rats was done with the EHBS for 4 weeks. The results indicated that the EHBS leaves, in comparison with metformin, had profound hypoglycemic and hypolipidemic activities. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14487 Bangladesh Pharmaceutical Journal 16(1): 27-31, 2013